Advanced Real Time Imaging II Cutting-Edge Techniques in Materials Science Studies - Nakano, Jinichiro; Pistorius, P Chris; Tamerler, Candan; Yasuda, Hideyuki; Zhang, Zuotai; Dogan, Neslihan; Wang, Wanlin; Saito, Noritaka; Webler, Bryan (The Minerals, Metals & Materials Series,, 2019)
"Real time" imaging techniques have assisted materials science studies especially for non-ambient environments. These techniques have never been collectively featured in a single venue. The book is an assembly of materials studies utilizing cutting edge real time imaging techniques, emphasizing the significance and impact of those techniques.